Change Detection on Remote Sensing Images Using Multidimensional Attention Network - Yiming Zhang; Mingliang Xue; Yao Lu; Xuan Liang; Pengyuan Niu; Xueqian Wang; You He (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Change detection (CD) in remote sensing images plays a vital role in applications such as urban planning and land resource management. Despite its importance, challenges persist due to complex backgrounds, which often lead to imprecise edge detection and missed small-scale target changes. These limitations highlight the need for methods that can robustly extract fine-grained details without sacrificing computational efficiency. To address these challenges, this study proposes a multidimensional attention network (MDANet) for CD in remote sensing imagery. It incorporates a novel multidimensional attention mechanism that effectively captures fine-grained details for small object detection, while maintaining computational efficiency and robustness in handling complex scenes. First, it introduces the attention feature fusion module, which extracts critical channel features and locates regions of interest to preserve detail and improve edge precision. Second, the multiscale feature enhancement module is employed, integrating multiscale convolution branches to capture a broader context, thus addressing the issue of missing small-scale changes. The proposed MDANet was tested on three widely used datasets—LEVER-CD, WHU-CD, and SVCD—and showed better performance compared to existing state-of-art methods. Results indicate that MDANet effectively detects small-scale object changes, achieving superior overall accuracy compared to other competing methods.